Gastrointestinal stromal tumor of large size, extragastrointestinal localization and different morphological features. - Shpon’ka, I. S.; Grycenko, P. O.; Skoryk, V. R. (Medicni Perspektivi, 2015)
The problems of accurate verification of the gastrointestinal stromal tumor are relevant today for many reasons. Thus, the histological diagnosis is complicated by the morphological similarity of other gastrointestinal tract mesenchymal neoplasms and by histologicaly different zones within the same investigation. We present the situation with the above issues: the differential diagnosis includes an analysis of morphological criteria and received immunohisto-chemical reactions. Between immunophenotypes of histologicaly different zones principal difference is not revealed.